Effect of Dietary Fiber Source on Growth Performance, Carcass Characteristics, and Economic Return of Finishing Pigs - K. M. Dunmire; L. L. Thomas; M. B. Braun; C. N. Truelock; M. D. Tokach; J. M. DeRouchey; R. D. Goodband; J. C. Woodworth; S. S. Dritz; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 287 pigs (DNA 600 × 241; initially 111.8 lb) were used in an 86-d experiment to determine the effect of dietary fiber source on finishing pig growth performance and carcass characteristics. There were 12 pens per treatment with 7 or 8 pigs per pen. Pens were randomly assigned to 1 of 3 dietary treatments consisting of a control (8.7% neutral detergent fiber; NDF), 20% dried distillers grains with solubles (DDGS; 13.6% NDF), or 14.5% sugar beet pulp (SBP; 13.6% NDF). Experimental diets were fed from d 0 to 86 in 3 phases; d 0 to 18, d 18 to 39, and d 39 to 86. From d 0 to 86, there was no evidence for treatment difference in ADG or ADFI. Pigs fed DDGS had marginally poorer F/G than the control or 14.5% SBP diets (P<0.10). Caloric efficiency of net energy (NE) in kcal per lb of live gain was marginally poorer (P<0.10) in pigs fed DDGS compared to those fed control and SBP. There was a decrease (P<0.10) in hot carcass weight (HCW) and carcass yield (P<.0.05) in pigs fed DDGS and SBP compared to those fed the control diet. Loin depth marginally decreased (P<0.10) in pigs fed SBP compared to the control, with those fed DDGS intermediate. Feed cost per pig was greatest (P<0.05) for pigs fed SBP, followed by DDGS, with those fed the control diet having the least. Feed cost per lb of gain increased (P<0.05) in pigs fed SBP, followed by DDGS, with those fed the control having the least. Gain value decreased (P<0.05) in pigs fed SBP compared to the control, with those fed DDGS intermediate. Income over feed cost was poorest (P<0.05) in pigs fed SBP, followed by DDGS, with those fed the control diet being the greatest. In conclusion, pigs fed DDGS tended to have poorer F/G compared to those fed the control diet or SBP. This can be explained by the overestimation of NE of the diet as demonstrated by an increase in caloric efficiency. Increasing dietary NDF reduced carcass yield and economic return.
Keywords: Fiber; sugar beet pulp; DDGS; finishing pigs